2015
DOI: 10.1249/mss.0000000000000547
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Is Associated with a Reduction in Gestational Diabetes Mellitus

Abstract: The exercise program performed during pregnancy reduced the prevalence of GDM by preserving glucose tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
123
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 33 publications
3
123
0
1
Order By: Relevance
“…Although not all GDM events can be prevented, lifestyle interventions introduced early in pregnancy or before pregnancy have the potential of preventing GDM development, at least among some women. This is supported by the promising findings from large observational studies on pre-pregnancy diet and lifestyle (Table 1), aforementioned positive findings from studies that started the intervention early in pregnancy [31][32][33][34][35][36][37][38][39][40], and by the successful prevention of type 2 diabetes with diet and lifestyle modification among non-pregnant individuals, for example, in the FDPS [26] and in the US DPP [27]. Finally, findings from animal and human medical studies have demonstrated the biological plausibility of improving insulin sensitivity and secretion through diet and lifestyle modification.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Although not all GDM events can be prevented, lifestyle interventions introduced early in pregnancy or before pregnancy have the potential of preventing GDM development, at least among some women. This is supported by the promising findings from large observational studies on pre-pregnancy diet and lifestyle (Table 1), aforementioned positive findings from studies that started the intervention early in pregnancy [31][32][33][34][35][36][37][38][39][40], and by the successful prevention of type 2 diabetes with diet and lifestyle modification among non-pregnant individuals, for example, in the FDPS [26] and in the US DPP [27]. Finally, findings from animal and human medical studies have demonstrated the biological plausibility of improving insulin sensitivity and secretion through diet and lifestyle modification.…”
mentioning
confidence: 61%
“…The few studies that did demonstrate a significant beneficial effect of diet and/or physical activity all started the intervention relatively early, in the first trimester, before or near 13 weeks of gestation [31][32][33][34][35][36][37][38][39][40]. For example, among all the published studies to date on physical activity interventions for GDM prevention [41,42], the point estimate for the majority of studies indicate a beneficial effect, yet only those with the intervention starting early in the first trimester had statistically significant findings [33][34][35]38]. The same was true for intervention approaches that combined physical activity with diet modification [36,37,40], administered diet modification/supplement alone [39] or pharmacological intervention with metformin [31].…”
mentioning
confidence: 99%
“…Building on these findings, a 2015 study conversely found a significant reduction of risk (90%, Odds ratio = 0.10, P = 0.09) for GDM, as well as a reduction in Oral Glucose Tolerance Test at 180 minutes post intake with the exercise group (intervention 98 mg/dL vs. 116.25 mg/dL Control) [18]. Overall this study was still relatively small and did not mention nutrition as an influence of outcomes [18]. Prior to this influential study, another group reviewed 1241 Hispanic women and reviewed self-reported exercise levels at prepregnancy, early and mid-pregnancy [19].…”
Section: Discussionmentioning
confidence: 93%
“…Despite this being a large study, the data was collected retrospectively and a significant portion was survey-based thus leaving it open to patient interpretation [17]. Building on these findings, a 2015 study conversely found a significant reduction of risk (90%, Odds ratio = 0.10, P = 0.09) for GDM, as well as a reduction in Oral Glucose Tolerance Test at 180 minutes post intake with the exercise group (intervention 98 mg/dL vs. 116.25 mg/dL Control) [18]. Overall this study was still relatively small and did not mention nutrition as an influence of outcomes [18].…”
Section: Discussionmentioning
confidence: 98%
“…Exercise increases the rate of glucose uptake in the skeletal muscle; a process that is regulated by the GLUT 4 transporter improves glycemic control and insulin sensitivity [42,43]. Both fasting and postprandial blood glucose concentrations can be reduced by exercise in women with GDM [44].…”
Section: Treatment Of Gdmmentioning
confidence: 99%